Understanding raciolinguistic dynamic in EFL classroom: a systematic literature review on language and identity in global educational contexts - Nirwana; Gunawan, Wawan; Muhlis (JOALL (Journal of Applied Linguistics and Literature), 2025)
This research aims to explore and analyze the raciolinguistic dynamics that influence teaching and learning experiences, as well as educational access, within global EFL contexts. Through an in-depth review of current literature, this research explores how language biases and hierarchies influence educational structures, create inequalities and affect social mobility. The study not only highlights the issues of raciolinguistic but also expands critical understanding of the role of language in reproducing or undermining social injustice. The research shows how raciolinguistic ideas have been globalized and adapted to a variety of circumstances by utilizing bibliometric analysis of the Scopus database and applying it to a wide range of previously published works. It also highlights the need for educational practices that bring these ideas into play to solve racial and linguistic disparities. The results show that racialolinguistic ideas are not only globally spread, but also adapted in various educational contexts, reflecting how language policies and pedagogical practices can reinforce or challenge social injustice. Using a cross-country survey and case studies, this study identifies adaptive strategies used in EFL teaching to deal with linguistic and racial challenges. In addition, the findings emphasize the importance of policy-based approaches and more inclusive pedagogies to reduce language and racial disparities in education. By cross-national surveys and case studies, the study emphasizes the significance of adaptive techniques and the complex interactions between language and race in EFL classroom.